Internalisasi Peran Ibu dalam Mengembangkan Konsep Fitrah pada Diri Anak di Era Digitalisasi Dakwah - Linda Ayu Karisma (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2024)
Abstract This study aims to analyze the internalization of the mother's role in developing the concept of fitah in children in the current era of digitalization of da'wah. The method used in this research uses descriptive qualitative research with the leterature review method. The sources used are several journals, books, and documents as well as sources of data or information that are considered relevant to this research. This research was conducted by collecting, managing and summarizing from 20 national journals that are relevant to the keywords then interpreting them into unique new findings. The results showed that: 1) There are 7 fitrahs owned by humans, including the fitrah of faith, survival, learning to serve, love, interaction, sexuality, and responsibility. 2) The role of mothers in developing children's fitrah can be done as exemplified by the Prophet, including exemplary, habituation, advice, monitoring/supervision, and punishment. 3) Digitalization of da'wah as a strategy in the process of internalizing the role of mothers can be done by utilizing social media, namely YouTube and Instagram.